ANALYSIS POLITENESS STRATEGY OF PRABOWO SUBIANTO SPEECH ON THE CSIS INDONESIA EVENT - Lingga, Fitri Ajelita; Christina Natalina , Christina Natalina (Dharmas Education Journal (DE_Journal), 2024)
This research is entitled "Analysis Politeness Strategy of Prabowo Subianto Speech on the CSIS Indonesia Event". This research aims to analyze the employment of politeness strategies by Prabowo Subianto in his speech at the CSIS Indonesia event using Brown and Levinson's theory as the analytical framework. The research design used was descriptive qualitative method. The results of this study identified four types of politeness strategies: 31 utterances using Bald on Record strategy (43.06%), 29 utterances using Positive Politeness strategy (40.28%), 6 utterances using Negative Politeness strategy (8.33%), and 6 utterances using Off Record strategy (8.33%). Based on the analysis, Bald on Record (43.06%) is the most dominant type of politeness strategy. From this finding, it can be concluded that Prabowo Subianto often expressed This shows that Prabowo tends to speak directly and firmly without paying much attention to aspects of gentleness or adjustments to the listener. This approach suggests that Prabowo Subianto may have a tendency to emphasize clarity and decision in his communication. He may prefer to deliver his message directly without much "playing around" with words or cloaking his intentions with various politeness strategies.